Peran analisa urin pada penanganan penyakit ginjal dan traktus urinarius - Ricke Loesnihari (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Renal and urinary tract diseases can caused severe problem if its diagnose late. That is because Renal organs have ability to compensate and human can live normally with one renal organ. Urinalysis test as a screening test can be performed without any indication and there are parameters which are represent so many condition that are affected by renal function. Abnormal urinalysis may indicate renal and urinary tract disease or renal damage caused by other disease. The source of uncertain component in urine specimen were estimated on biological variation or influenced by end product of metabolism and the question is whether or not this approach represents good laboratory practice should be identified. In conclusion, urinalysis could detect chronic renal disease in its early stage and also good laboratory practice could give reliable result. Keywords: renal; urinalysis; proteinuria; urine sediment